2022
DOI: 10.22323/2.21010206
|View full text |Cite
|
Sign up to set email alerts
|

Scientific research in news media: a case study of misrepresentation, sensationalism and harmful recommendations

Abstract: Accurate news media reporting of scientific research is important as most people receive their health information from the media and inaccuracies in media reporting can have adverse health outcomes. We completed a quantitative and qualitative analysis of a journal article, the corresponding press release and the online news reporting of a scientific study. Four themes were identified in the press release that were directly translated to the news reports that contributed to inaccuracies: sensationalism, misrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…22 These findings are in line with previous coverage of the 2019 European heat waves, which found that the news media highlighted record-breaking temperatures, followed by the impact of the heat wave on critical infrastructure (eg, transport, energy) 23. Focusing on record-breaking temperatures or the infrastructure impacts of an EHE is in line with news values , which refers to criteria that influence the selection and presentation of events as published news 24. However, with the public receiving a significant amount of their health information from the media,25 a greater balance is needed between reporting reactive content (eg, impacts to critical infrastructure) and proactive content (eg, heat-protective messaging).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…22 These findings are in line with previous coverage of the 2019 European heat waves, which found that the news media highlighted record-breaking temperatures, followed by the impact of the heat wave on critical infrastructure (eg, transport, energy) 23. Focusing on record-breaking temperatures or the infrastructure impacts of an EHE is in line with news values , which refers to criteria that influence the selection and presentation of events as published news 24. However, with the public receiving a significant amount of their health information from the media,25 a greater balance is needed between reporting reactive content (eg, impacts to critical infrastructure) and proactive content (eg, heat-protective messaging).…”
Section: Discussionsupporting
confidence: 78%
“…For example, 57 terms were used to describe the signs of HRI, some of which used language that may not be understood by the public (Table S2). Complex language may confuse and impact awareness of heat-related risks 24. For example, “hyperthermia” [28], “heat tetany” [29], and “heat syncope” [30] were cited within the articles.…”
Section: Discussionmentioning
confidence: 99%
“…Constant association of these apps in the media as tools that White, educated and upper/middle-class people could benefit from, without mentioning the lack of diversity in research, can further perpetuate historical and ongoing disparities in psychological research, wherein most studies primarily involve WEIRD (Western, educated, industrialised, rich and democratic) populations (Rad et al, 2018). It is therefore critical that journalists consider the limitations of studies when presenting findings from health research to avoid sensationalism, misrepresentation and harmful recommendations (Dempster et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Journalists in local mass media will get the truth in their area faster than national media journalists, who do not necessarily know the area of the incident. National journalists sometimes only rely on press releases issued by institutions which sometimes do not match the facts on the ground or are interpreted incorrectly by journalists (Dempster et al, 2022).…”
Section: Hoax Sensitive Journalistmentioning
confidence: 99%